Moving object detection and tracking from video sequence : an analysis between canny edge detection and active contour technique / Mohd Anuar Mohd Salleh - Mohd Salleh, Mohd Anuar (2006)
Application of tracking is to monitor scenes where one would ideally have one or more human observers identifying events and noting everything that happens. In this research, a system to detect moving object in video sequence was develop and Canny edge detection and active contour technique has been chosen to test the effectiveness of this technique. Canny edge detection and active contour was developed using C++ language. The algorithm was tested on standard image processing benchmarks and significances of the result are discussed. Keywords: caimy edge detection, active contour, backgroimd subtraction